2022
DOI: 10.3390/nu14071427
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Overweight/Obesity, Anemia and Micronutrient Deficiencies among Non-Pregnant Women of Reproductive Age in Ghana: Results from a Nationally Representative Survey

Abstract: Overweight/obesity (OWOB) often co-occurs with anemia or micronutrient deficiencies (MNDs) among women of reproductive age (WRA) in Ghana; identifying the risk factors of these conditions is essential for prevention. We aimed to examine the prevalence of OWOB, anemia, and MNDs and their co-occurrence and risk factors among non-pregnant women 15–49 years of age in Ghana. Data were from a 2017 two-stage national survey of 1063 women. We estimated the weighted prevalence of single and co-occurring malnutrition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 47 publications
(49 reference statements)
4
16
0
Order By: Relevance
“…These levels of obesity and anemia in Volta region cast doubt that obesity reduces anemia risk. Nonetheless, elsewhere, in Saudi Arabia obese pregnant women, about three-fifths were anemic [48], whereas analysis of a National data from Ghana indicated below 10% co-occurrence of overweight/obesity and anemia in WIFA, [36] but more than half were shown to have co-occurrence of overweight and anemia [35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These levels of obesity and anemia in Volta region cast doubt that obesity reduces anemia risk. Nonetheless, elsewhere, in Saudi Arabia obese pregnant women, about three-fifths were anemic [48], whereas analysis of a National data from Ghana indicated below 10% co-occurrence of overweight/obesity and anemia in WIFA, [36] but more than half were shown to have co-occurrence of overweight and anemia [35].…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with National surveys. In particular, the Ghana Demographic Health Survey data revealed a higher burden of maternal malnutrition, varying substantially by individual nutritional status, economic status, parity, and ethnicity [14,35,36]. These are paradoxically linked predisposition factors of malnutrition common to LMICs [1,4,37].…”
Section: Discussionmentioning
confidence: 99%
“…In a regional study in Latin America in 3254 women aged 15 to <45 years, Herrera-Cuenca et al [ 41 ] found that 58.7% were overweight, associated with adequate iron intake. Christian et al [ 42 ] conducted a national study in Ghana in 1063 women aged 15–49 years and found that the prevalence of overall overweight was 39%, anemia 22%, and deficiency of a micronutrient 62%.…”
Section: Discussionmentioning
confidence: 99%
“…Folate deficiency was observed in 18% of research participants, comparatively lower than other African studies, where folate deficiency was noted in 54% obese and non-obese women in Ghana ( 39 ). The Ghanaian study ( 40 ) notes that folate deficiency may be particularly high in West Africa where folate-deficient diets are consumed. In the same way, Modjadji et al ( 41 ) demonstrated low folate levels in 28% of non-pregnant women of childbearing age in Limpopo, South Africa.…”
Section: Discussionmentioning
confidence: 99%